Microbiome Composition and Dynamics of a Reductive/Oxidative Bioelectrochemical System for Perchloroethylene Removal: Effect of the Feeding Composition - Di Franca, Maria L.; Matturro, Bruna; Crognale, Simona; Zeppilli, Marco; Dell’Armi, Edoardo; Majone, Mauro; Petrangeli Papini, Marco; Rossetti, Simona (Frontiers in Microbiology, 2022)
Chlorinated solvents still represent an environmental concern that requires sustainable and innovative bioremediation strategies. This study describes the microbiome composition of a novel bioelectrochemical system (BES) based on sequential reductive/oxidative dechlorination for complete perchloroethylene (PCE) removal occurring in two separate but sequential chambers. The BES has been tested under various feeding compositions [i.e., anaerobic mineral medium (MM), synthetic groundwater (SG), and real groundwater (RG)] differing in presence of sulfate, nitrate, and iron (III). In addition, the main biomarkers of the dechlorination process have been monitored in the system under various conditions. Among them, Dehalococcoides mccartyi 16S rRNA and reductive dehalogenase genes (tceA, bvcA, and vcrA) involved in anaerobic dechlorination have been quantified. The etnE and etnC genes involved in aerobic dechlorination have also been quantified. The feeding composition affected the microbiome, in particular when the BES was fed with RG. Sulfuricurvum, enriched in the reductive compartment, operated with MM and SG, suggesting complex interactions in the sulfur cycle mostly including sulfur oxidation occurring at the anodic counter electrode (MM) or coupled to nitrate reduction (SG). Moreover, the known Mycobacterium responsible for natural attenuation of VC by aerobic degradation was found abundant in the oxidative compartment fed with RG, which was in line with the high VC removal observed (92 ± 2%). D. mccartyi was observed in all the tested conditions ranging from 8.78E + 06 (with RG) to 2.35E + 07 (with MM) 16S rRNA gene copies/L. tceA was found as the most abundant reductive dehalogenase gene in all the conditions explored (up to 2.46 E + 07 gene copies/L in MM). The microbiome dynamics and the occurrence of biomarkers of dechlorination, along with the kinetic performance of the system under various feeding conditions, suggested promising implications for the scale-up of the BES, which couples reductive with oxidative dechlorination to ensure the complete removal of highly chlorinated ethylene and mobile low-chlorinated by-products.